The influence of chemical reaction conditions upon poly(styrene‐methyl methacrylate‐acrylic acid) synthesis: Variations in nanoparticle size, colour and deposition methods. (30th December 2019) - Fernandes, Rui D. V.; Gomes, Pedro; Zille, Andrea; Souto, António P.
Abstract: Monodisperse latex nanospheres of poly(styrene‐methyl methacrylate‐acrylic acid) with different sizes were synthetised by soap‐free emulsion copolymerisation and applied onto polyamide 6, 6 fabrics by two methods, ie, gravitational sedimentation and dip‐drawing. Different‐sized nanospheres were synthetised by varying temperature and stirring velocity as reaction parameters. Scanning electron microscopy and scanning transmission electron microscopy were used to evaluate nanosphere sizes and deposition structures. The results showed two different nanosphere structural arrangements on the fabric surface, a hexagonal packed centre structure in the even surfaces and a square arrangement in the out‐of‐plane surfaces. Different colours were observed according to particle size, namely, violet ( ca . 170 nm), blue ( ca . 190 nm), green ( ca . 210 nm), yellow ( ca . 230 nm) and red ( ca . 250 nm). An iridescence effect was also observed, displaying different colours at different observation angles. By controlling the size of the nanospheres it was possible to obtain different, brilliant and iridescent colours. Using different nanosphere sizes it was possible to obtain different interplanar distances and to control the light scattering in the crystalline lattice planes, obtaining Bragg diffraction patterns.